Evaluating the implementation of inclisiran in primary care: process evaluation interim findings from interviews with key stakeholders - Peter Bower; Samantha Dixon; Paul Wilson; Amy Mathieson; Rebecca Elvey; Martin Gibson; Tracey Vell (BMJ Open)
Objectives VICTORION-Spirit was a hybrid study designed to assess the feasibility of implementing inclisiran, a novel cholesterol-lowering treatment and behavioural support within primary care centres in England. This process evaluation aimed to evaluate the implementation of inclisiran for patients with elevated low-density lipoprotein cholesterol and atherosclerotic cardiovascular disease (ASCVD) or ASCVD-risk equivalents (n=900), from the perspectives of key stakeholders.Design VICTORION-Spirit was a phase IIIb, multicentre, randomised, controlled study. We followed a process evaluation strategy to collate the views of stakeholders via semistructured interviews and to gain insights on the ‘implementability’ of inclisiran in primary care. Data were generated via interviews with patients, healthcare providers and research nurses and analysed using a qualitative rapid analysis approach.Setting Primary care in Greater Manchester, UK.Participants 84 participants were interviewed, including patients (n=56), professionals at participating practices in VICTORION-Spirit (n=13), health advisors (n=4) and research nurses (n=11).Results Interim findings suggest the process of receiving and providing inclisiran during the study was ‘straightforward’, and the behavioural support provided to some patients was generally viewed favourably. Beyond the trial, patients and healthcare providers thought the delivery of inclisiran could work well as a practice nurse-provided service. Barriers to implementing inclisiran were generally related to workforce and workload pressures in primary care, and an incentive structure to support delivery was recommended.Conclusions Patients and healthcare providers supported implementing inclisiran in primary care. It was convenient for patients to receive inclisiran in general practice, and most providers felt that the intervention was a useful addition to existing lipid-lowering treatments. Several barriers to implementation were highlighted, including concerns relating to general practice resources and costs.Trial registration number NCT04807400.